Public Primary School Teachers’ Perception Towards Child Abuse Reporting Practices in Nigeria - Adamu, Chidubem Deborah (PrimaryEdu : Journal of Primary Education, 2025)
At elementary schools, cases of child abuse are common among pupils, putting teachers in a challenging situation when it comes to reporting such cases. This study aimed to identify the child abuse reporting practices and perceptions of teachers regarding reporting practices in public elementary schools in the Alimosho Local Council Development Areas (LCDA) of Lagos State, Nigeria. A multi-stage sampling procedure was used to select a sample of 314 public primary school teachers in the study area through a cross-sectional survey research design. Data was collected using a self-structured questionnaire, and both descriptive and inferential statistics were used in the data analysis. The results showed that only 15.2% of teachers in the research area had a negative view of child abuse reporting practices, while the majority (84.8%) had a positive opinion. Additionally, a strong negative correlation (r = -0.254, p-value = 0.000) was found between teachers’ perceptions and child abuse reporting practices in public elementary schools in Alimosho LCDA. Based on the study’s findings, it is recommended that the government and school administration provide psychological training and a support system on child abuse to improve teachers’ attitudes toward reporting child abuse.